Association of loneliness with the risk of pain in older Chinese adults - Aijun Song; Siying Yu; Yao Shen; Zongyan Guo; Jian Shi (Scientific Reports)
Abstract This study investigates the long-term effects of loneliness on pain experiences in older Chinese adults, focusing on the mediating role of depression. Data from the China Health and Retirement Longitudinal Study (2013–2020) included 1,592 participants aged 60 and above. Using robust mixed-effects logistic regression models, the study found that lonely participants were more likely to experience 12 site pain: headache (OR 1.23; 95% CI 1.09–1.39), shoulder (OR 1.16; 95% CI 1.04–1.30), wrist (OR 1.14; 95%CI 1.01–1.28), finger (OR 1.14, 95% CI 1.02–1.28), chest (OR 1.26; 95% CI 1.10–1.44), stomach (OR 1.28, 95% CI 1.12–1.46), back (OR 1.23; 95% CI 1.00–1.51), waist (OR 1.46; 95% CI 1.17–1.83), buttock (OR 1.15, 95% CI 1.02–1.30), leg (OR 1.20, 95% CI 1.08–1.33), knee (OR 1.16; 95% CI 1.04–1.30), and toe (OR 1.18; 95% CI 1.04–1.34) than participants who were not lonely. No such finding was found for neck, arm, or ankle pain. The risk of pain due to loneliness did not decrease with an increase in the frequency of social activities. These findings emphasize the need to address mental health as a crucial factor in pain prevention and management.